Test Instrument to Measure Student’s Level of Chemical Literacy in Macromolecules Topic - Oktrilina Amelia; Risnita Vicky Listyarini (Jurnal Pendidikan Indonesia, 2022)
The science literacy level of students can be determined using a measuring instrument, namely a test instrument that includes four aspects of chemical literacy in each item. This study aims to develop a test instrument that is used to measure the achievement of a student's chemical literacy level. The research method used is the Model of Educational Reconstruction (MER). The limited trial of the test instrument was implemented for twelve students in the senior high schools. Data collection was carried out based on validation sheets of test instruments from expert validation, pretest and posttest. Data analysis for the test instrument is based on validation of the test instrument using Aiken’s V formula. Based on the correlation coefficient analysis of the test instrument resulted in 20 valid question items with a correlation coefficient value of 30.8% having moderate validity criteria, 7.7% having high criteria and 12.8% having very high criteria. The reliability test shows that the test instrument is reliable and has a high correlation with the Cronbach Alpha value of of 0.920. The difficulty level of the question and the discriminatory of the question were determined. The results of the student response questionnaire to the test instrument have an average percentage of 79% with practical criteria. This research concludes that the test instruments can be used to measure the level of chemical literacy of students. The chemical literacy level of students at the low level and the nominal level of scientific literacy is the highest level the students can achieve.